2010
DOI: 10.1093/jmedent/47.1.22
|View full text |Cite
|
Sign up to set email alerts
|

Biting Activity of Mosquito Species (Diptera: Culicidae) in the Turkey-Armenia Border Area, Ararat Valley, Turkey

Abstract: During nine consecutive nights in July 2007 (from 18:15-05:45 h), mosquitoes landing-biting on humans were collected outdoors and indoors at the Turkey-Armenia border. A total of 1005 females were collected consisting of nine species. The dominant species was Aedes dorsalis (Meigen) (47.5% of total catch), followed by Anopheles hyrcanus (Pallas) (22.9%), Culex theileri (Theobald) (9.3%),Ae. vexans (Meigen) (6.6%), Ae. caspius (Pallas) (4.9%),Anopheles maculipennis s.l. (Meigen) (3.1%), Culex territans (Walker)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…It is possible that the incidence and diversity of zoonotic and arthropod vector-borne infections are higher in rural regions of the country, where agricultural practices, as well as ecological and climatic conditions, offer an environment favorable for disease transmission. A recent study conducted in the Turkey–Armenia border area reported the presence of multiple mosquito species that are potential vectors of several pathogens [19]. Our findings may not represent the full diversity and burden of the zoonotic and arthropod vector-borne diseases in Armenia.…”
Section: Discussionmentioning
confidence: 64%
“…It is possible that the incidence and diversity of zoonotic and arthropod vector-borne infections are higher in rural regions of the country, where agricultural practices, as well as ecological and climatic conditions, offer an environment favorable for disease transmission. A recent study conducted in the Turkey–Armenia border area reported the presence of multiple mosquito species that are potential vectors of several pathogens [19]. Our findings may not represent the full diversity and burden of the zoonotic and arthropod vector-borne diseases in Armenia.…”
Section: Discussionmentioning
confidence: 64%
“…In most cases, the resources that larvae consume in natural systems have not even been identified. Finally, many investigators have estimated mosquito biting rates in the field, [40][41][42][43][44][45][46] but few have defined details of biting behavior that we identified as important in our sensitivity analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The last clock describes the frequency at which mosquitoes get infected. It has a large variance depend on the species-e.g.. [3]. For Aedes aegypti, it can be larger due to the fact that its feeding is easily disturbed, and hence it might need to bite many hosts in order to complete its feeding [43].…”
Section: Introductionmentioning
confidence: 99%